Incidence of short estrous cycles after weaning in beef cows - Ward, S.; Odde, Kenneth G.; Kiracofe, G.; McKee, M. (Kansas State University. Agricultural Experiment Station, 2011)
Weaning calves from cows that had not cycled after calving caused a higher percentage of cows to show estrous in the next 25 days than cows suckling calves. However, 78.3% of the nonsuckling cows had short cycles (7-10 days) compared with 16.6% of the cows suckling calves. A short cycle does not appear to be clinically abnormal when estrus occurs with the first ovulation after calving. The percentage of cows having an estrus with the first ovulation, and thus a short cycle, increases drastically when calves are weaned. Although anestrous cows can be induced to cycle by weaning their calves, the first estrus after weaning is relatively infertile.
Keywords: Beef; Estrus; Weaning